(untitled) (Ibrahim Cardiac Medical Journal, 2015)
Objective: To determine the outcome of primary percutaneous coronary intervention (PPCI) in Ibrahim Cardiac Hospital & Research Institute. Methods: Medical records of 66 consecutive patients presented in our hospital between January 2010 toJune,2011 with acute ST elevation myocardial infarction (STEMI) and were treated with primary PCI as a mode of reperfusion were reviewed. The primary end point was in hospital mortality and secondary end points were 30 day mortality, myocardial infarction, recurrent angina and congestive cardiac failure, from discharge to one month follow up. Results: The procedural success was 98.5%. One (1.5%) patient died during hospital stay .No mortality was observed in the 30 days follow up from discharge while other complications like recurrent angina and acute left ventricular failure were 1.5%. Conclusions: Our findings suggest favorable outcomes, matching the international data can be achieved in our patients with primary PCI in the management of life threatening illness like STEMI despite all the limitations. Primary PCI as a preferred method of reperfusion strategy needs to be practiced more often in our part of the world. Ibrahim Cardiac Med J 2013; 3(1&2): 10-14